A eudaimonia na ética das virtudes de Aristóteles - Pequeno, Noêmia de Mendonça Lins (2014)
The following dissertation aims to undertake a philosophical study, supported by incursions of context referring to the ancient Greek world historical and political. The study is able to provide us with a greater theoretical understanding of eudaimonia, coming from an ethics of virtues, according to Aristotle, it would be possible for those who acted according to the demands of an excellent action. Such research will be based largely on analytical readings from the work of Aristotle, in particular, the Nicomachean Ethics, as well as Socratic -Platonic texts that supported the Greek ethos. Moreover, the text will report to the works of interpreters and researchers on the field, able to assist us during this endeavor. Thus, we seek to understand, in Aristotelian ethics, the ability of humans to an action based on a kind of wisdom can be ethical values from their own ability to decide on the facts that are presented to him. Therefore, since they are subject to the contingency that human action is subject, should be covered by the experience of every one who, being obliged to action, must act with practical wisdom inherent in the prudent man.